Relationship Between Laptop Use Behavior and Health in Midwifery Students at the University of West Sumatra: Hubungan Antara Perilaku Penggunaan Laptop Dengan Kesehatan Pada Mahasiswa Kebidanan Universitas Sumatera Barat - Ranne Balqis; Weddy Martin; Tri Monarita Johan; Puthi Dwi Unthari (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2022)
The use of laptops is generally to meet the needs of wireless communication and internet access. The use of laptops has increased very high in the world of education, both among school and college students. The majority of today's school children always bring laptops to school because of the demands of an increasingly sophisticated era. In the world of education, Australia is a pioneer country for the use of laptops in the school environment, laptops are in great demand because they can be used anywhere and also the use of laptops has a positive impact on the learning and teaching process. The data collection method was carried out by interviews using a research instrument in the form of a questionnaire. The results of this study showed that there was no significant relationship between laptop size and health complaints that were felt due to laptop use (Pvalue = 0.961), there was no significant relationship between the duration of laptop use and health complaints that were felt due to laptop use (Pvalue = 0.782), no there is a significant relationship between the frequency of laptop use and health complaints that are felt due to laptop use (Pvalue = 0.065), there is a significant relationship between body position when using a laptop and health complaints that are felt due to laptop use (Pvalue = 0.002).